Water Absorption, Tensile Strength, Cooking Loss of Wet Noodles With Gadung Flour Substitution Using CMC - Putri, Soraya Kusuma; Siqhny, Zulhaq Dahri (Program Studi Teknologi Pangan, 2023)
Gadung tubers, as well as gadung flour, can be used to make a variety of alternative processed foods. Flour with a high protein content is required because the protein content affects the texture, particularly the elasticity and crunchiness of the noodles. In addition, the use of CMC in making noodles can make the noodles elastic and not mushy. CMC functions to trap water molecules in the gel structure formed by CMC, so that the resulting noodles become more chewy and elastic. This study aimed to determine the physical properties (water absorption, cooking loss, tensile strength) the noodles using a randomized block design (RBD) with one factorial. The ratio of gadung tuber flour to wheat flour was ranged at four levels, namely 90:10, 80:20, 70:30, 60:40, and 50:50, with the addition of CMC up to 1% of a total weight for an overall mass of 100 g of flour mixture, and three repetitions. Based on the results showed the highest water absorption and cooking loss in the proportion of wheat flour: gadung flour 50: 50, namely 12.365% and 1.07%, respectively, while the highest results in tensile strength were obtained in the proportion of wheat flour: gadung flour 90: 10, namely 0.174Mpa.Â